Dampak Sosial Ekonomi Pelaku Usaha Pasca Relokasi dari Wisata Pantai Mandra Kabupaten Kolaka (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
This study examines the socio-economic impacts experienced by micro, small, and medium enterprises (MSMEs) following their relocation from the Mandra Beach tourism area in Kolaka Regency. The relocation policy was implemented by the Kolaka Regency Government as part of an effort to reorganize the coastal area, with considerations for preserving cultural icons (the Mekongga Traditional House), restoring public space functions, and addressing sanitation issues. Using a descriptive qualitative approach with a phenomenological method, this research analyzes changes in income and social interaction patterns among business actors before and after the relocation. The findings reveal a significant decline in business income post-relocation, driven by reduced visitor numbers and the less strategic nature of the new location. Social interactions among business actors remained harmonious, yet interactions with customers became more transactional. Communication between business actors and the government was largely one-way, creating uncertainty among traders. This study recommends strengthening participatory communication from the government and fostering innovative adaptation among business actors to support the sustainability of the local economy.